Analysis of the Implementation of Customer Relationship Management to Increase Customer Loyalty and Satisfaction at PT. Tunas Toyota Cilegon - Nur Aini Azzahra; Anas Hidayat (Publikasi Inspirasi Indonesia, 2024)
Nowadays, the level of business competition, especially in the automotive industry, continues to grow rapidly, so that every day companies have to think about ways to maintain existing companies by continuing to innovate and create good systems for the running of the company. Therefore, companies need to carry out activities, one of which is in the field of marketing, in developing products and good quality. One way to create this system is to provide good service to customers in order to maintain relationships to increase customer loyalty. This research aims to analyze the strategy for implementing customer relationship management in increasing customer loyalty at PT. Tunas Toyota Cilegon. This company is a sales service for Toyota brand four-wheeled vehicles and provides spare parts, car service and test drives.PT. Tunas Toyota Cilegon has various facilities that can support the company’s performance, such as the availability of a showroom, body repair, service and spare parts, workshop, body and painting, and repainting. PT. Tunas Toyota Cilegon is located at Jl. Raya Cilegon Km.14 Cibeber Cilegon City Banten Province. The type of research used in this research is qualitative research. The research was carried out at PT. Tunas Toyota Cilegon by selecting 5 informants related to the theme of this research. The data collection techniques used were interview techniques, book observations, and documentation. The results of this research show that implementing a customer relationship management (CRM) strategy can help increase customer loyalty. Therefore, it can be said that this CRM strategy is an effective strategy in increasing and maintaining loyalty customer.